Consideration of a New Liquidity Instrument for Market Access Countries. (Policy Papers; Policy Paper, 2006)
The objective of this paper is to consider key issues in the design of a new liquidity instrument for market access countries. It reviews the motivations and challenges of creating such an instrument and lays out options and issues related to four key design elements. Recognizing the need to consider the relationship between these elements, the paper sets out an example of how they might be combined in a lending instrument - called here the Reserve Augmentation Line, or RAL. It also discusses risks.